2019
DOI: 10.1002/pro.3636
|View full text |Cite
|
Sign up to set email alerts
|

Hsp104 facilitates the endoplasmic‐reticulum–associated degradation of disease‐associated and aggregation‐prone substrates

Abstract: Misfolded proteins in the endoplasmic reticulum (ER) are selected for ER-associated degradation (ERAD). More than 60 disease-associated proteins are substrates for the ERAD pathway due to the presence of missense or nonsense mutations. In yeast, the Hsp104 molecular chaperone disaggregates detergent-insoluble ERAD substrates, but the spectrum of diseaseassociated ERAD substrates that may be aggregation prone is unknown. To determine if Hsp104 recognizes aggregation-prone ERAD substrates associated with human d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 103 publications
(149 reference statements)
2
23
0
Order By: Relevance
“…Chaperone holdases are especially critical for retrotranslocated membrane proteins since they contain hydrophobic transmembrane domains and are consequently aggregation prone. Since yeast lack Bag6, Hsp104 facilitates the solubilization and retrotranslocation of aggregationprone ERAD substrates (Preston et al, 2018;Doonan et al, 2019).…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…Chaperone holdases are especially critical for retrotranslocated membrane proteins since they contain hydrophobic transmembrane domains and are consequently aggregation prone. Since yeast lack Bag6, Hsp104 facilitates the solubilization and retrotranslocation of aggregationprone ERAD substrates (Preston et al, 2018;Doonan et al, 2019).…”
Section: Retrotranslocation and Degradationmentioning
confidence: 99%
“…There was an increase in the abundance of Ssa1 and Ssa2, two Hsp70 family members in both mutants: ~1.5x increase in pup2ts and a ~2x increase in rpn5-ts. Ssa1/2 have been shown to play a role in delivering misfolded protein to the proteasome during ER-associated degradation (ERAD) (85) Additionally, Hsp104, another chaperone linked to ERAD, was seen to increase in protein abundance 1.7x and 1.4x in pup2-ts and rpn5-ts respectively (86). The upregulation of cellular chaperones could be a compensation mechanism for defects in 26S proteasome function and could help explain why these cells are able to survive at permissive temperature despite altered proteasomal activity.…”
Section: Multiomics Intersection Analysis Of Mtpp With Global Proteommentioning
confidence: 99%
“…CFTR is a 1480 amino acid anion channel containing two membrane-spanning domains (MSD1 and MSD2), two nucleotide-binding domains (NBD1 and NBD2), and a disordered regulatory R-domain. CFTR folding and misfolding is the topic of intense study, which has identified disease-causing mutations that cause arrested intermediates to accumulate in globally misfolded and aggregated states (Doonan et al, 2019). The F508del mutation is located in NBD1, so F508del-NBD1 is unstable and fails to correctly assemble with NBD2 and the cytoplasmic loops (CL) that lie in between CFTR's 12 transmembrane spans.…”
Section: Introductionmentioning
confidence: 99%